ELDORADO VERNACULAR: Barkerville and Its Buildings. - IREDALE, JENNIFER (BC Studies)
The article discusses the wooden vernacular architecture of Barkerville, British Columbia (BC) from the town's gold rush era of the 1860s, often referencing photographs from the period. An overview of the buildings constructed in Barkerville during the 1860s, including the reconstruction efforts following a major fire in 1868, is provided.